The Cytidine Deaminase APOBEC3 Family Is Subject to Transcriptional Regulation by p53 - Menendez, Daniel; Nguyen, Thuy-Ai; Snipe, Joyce; Resnick, Michael A. (Molecular cancer research, 2017)
The APOBEC3 (A3) family of proteins are DNA cytidine deaminases that act as sentinels in the innate immune response against retroviral infections and are responsive to IFN. Recently, a few A3 genes were identified as potent enzymatic sources of mutations in several human cancers. Using human cancer cells and lymphocytes, we show that under stress conditions and immune challenges, all A3 genes are direct transcriptional targets of the tumor suppressor p53. Although the expression of most A3 genes (including A3C and A3H) was stimulated by the activation of p53, treatment with the DNA-damaging agent doxorubicin or the p53 stabilizer Nutlin led to repression of the A3B gene. Furthermore, p53 could enhance IFN type-I induction of A3 genes. Interestingly, overexpression of a group of tumor-associated p53 mutants in TP53-null cancer cells promoted A3B expression. These findings establish that the "guardian of the genome" role ascribed to p53 also extends to a unique component of the immune system, the A3 genes, thereby integrating human immune and chromosomal stress responses into an A3/p53 immune axis. Implications: Activated p53 can integrate chromosomal stresses and immune responses through its influence on expression of APOBEC3 genes, which are key components of the innate immune system that also influence genomic stability. Mol Cancer Res; 15(6); 735–44. ©2017 AACR.